2018
DOI: 10.23887/jere.v2i1.12558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Problem Solving Learning Model on Students Achievement

Abstract: This research aims to determine the difference in student achievement that used problem solving learning model and conventional learning model. The type of research was quasi experimental. The research was conducted at SMP N 11 Manokwari. The sampling technique used purposive sampling. A number of the sample the control group of 31 students and the experimental group of 30 students. Data analysis used independent t-test at significant level 0,05 with help of SPSS 22 for Windows program. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
3
8
0
4
Order By: Relevance
“…The findings of this study are in line with the results of research by Nasreen and Shah (2019) or Hoque et al (2020) which showed that instructional supervision affects teacher motivation, attitudes, and teaching performance. When studied further, the application of constructivist-based learning models, namely cooperative learning, problem-solving, and work-based learning models has a strong effect on student motivation and achievement (Damopolli et al, 2018;Nasution, 2017;Sudjimat & Permadi, 2019). Likewise, the enrichment of various learning materials also has a significant effect on student achievement (Oladejo et al, 2011;Setyowati et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are in line with the results of research by Nasreen and Shah (2019) or Hoque et al (2020) which showed that instructional supervision affects teacher motivation, attitudes, and teaching performance. When studied further, the application of constructivist-based learning models, namely cooperative learning, problem-solving, and work-based learning models has a strong effect on student motivation and achievement (Damopolli et al, 2018;Nasution, 2017;Sudjimat & Permadi, 2019). Likewise, the enrichment of various learning materials also has a significant effect on student achievement (Oladejo et al, 2011;Setyowati et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Melalui penggunaan keahlian dari berbagai sumber informasi, siswa tahu bagaimana mengembangkan dan memperluas pengetahuan dan keahlian yang dimilikinya, yang bisa mereka gunakan baik di dalam maupun di luar sekolah. Menurut Damopolii, Nunaki, & Supriyadi (2018) bahwa guru tidak harus selalu menentukan pembelajaran sesuai selera mereka, akan tetapi sangat perlu melihat dari sisi siswa itu sendiri, pembelajaran seperti apa yang cocok dengan mereka.…”
Section: Pendahuluanunclassified
“…Dalam proses pembelajaran, belajar adalah proses seseorang untuk berubah baik dalam aspek pengetahuan, keterampilan, maupun sikap (Damopolii et al, 2018). Keberhasilan pembelajaran pada ranah pengetahuan dan keterampilan dipengaruhi oleh kondisi sikap peserta didik.…”
Section: Pendahuluanunclassified